An Extended Binaural Real-Time Auralization System With an Interface to Research Hearing Aids for Experiments on Subjects With Hearing Loss. (October 2018) - Pausch, Florian; Aspöck, Lukas; Vorländer, Michael; Fels, Janina
Theory and implementation of acoustic virtual reality have matured and become a powerful tool for the simulation of entirely controllable virtual acoustic environments. Such virtual acoustic environments are relevant for various types of auditory experiments on subjects with normal hearing, facilitating flexible virtual scene generation and manipulation. When it comes to expanding the investigation group to subjects with hearing loss, choosing a reproduction system which offers a proper integration of hearing aids into the virtual acoustic scene is crucial. Current loudspeaker-based spatial audio reproduction systems rely on different techniques to synthesize a surrounding sound field, providing various possibilities for adaptation and extension to allow applications in the field of hearing aid-related research. Representing one option, the concept and implementation of an extended binaural real-time auralization system is presented here. This system is capable of generating complex virtual acoustic environments, including room acoustic simulations, which are reproduced as combined via loudspeakers and research hearing aids. An objective evaluation covers the investigation of different system components, a simulation benchmark analysis for assessing the processing performance, and end-to-end latency measurements.